Structural and functional characterization of Mpp75Aa1.1, a putative beta-pore forming protein from Brevibacillus laterosporus active against the western corn rootworm. - Jean-Louis Kouadio (Public Library of Science (PLoS), 2021)
The western corn rootworm (WCR), Diabrotica virgifera virgifera LeConte, is a major corn pest of significant economic importance in the United States. The continuous need to control this corn maize pest and the development of field-evolved resistance toward all existing transgenic maize (Zea mays L.) expressing Bacillus thuringiensis (Bt) insecticidal proteins against WCR has prompted the development of new insect-protected crops expressing distinct structural classes of insecticidal proteins. In this current study, we describe the crystal structure and functional characterization of Mpp75Aa1.1, which represents the first corn rootworm (CRW) active insecticidal protein member of the ETX_MTX2 sub-family of beta-pore forming proteins (β-PFPs), and provides new and effective protection against WCR feeding. The Mpp75Aa1.1 crystal structure was solved at 1.94 Å resolution. The Mpp75Aa1.1 is processed at its carboxyl-terminus by WCR midgut proteases, forms an oligomer, and specifically interacts with putative membrane-associated binding partners on the midgut apical microvilli to cause cellular tissue damage resulting in insect death. Alanine substitution of the surface-exposed amino acids W206, Y212, and G217 within the Mpp75Aa1.1 putative receptor binding domain I demonstrates that at least these three amino acids are required for WCR activity. The distinctive spatial arrangement of these amino acids suggests that they are part of a receptor binding epitope, which may be unique to Mpp75Aa1.1 and not present in other ETX_MTX2 proteins that do not have WCR activity. Overall, this work establishes that Mpp75Aa1.1 shares a mode of action consistent with traditional WCR-active Bt proteins despite significant structural differences.